Development of interactive learning media based on augmented reality about animal to improve students' cognitive ability - Ayu Gde Chrisna Udayanie (Jurnal Mantik, 2023)
Education is essential to students' intellectual and social growth. Effective learning affects children's cognitive development. Tech-based learning can be new and participatory, therefore the research goal is to use AR to master complicated ideas like animal knowledge. AR-based interactive learning material lets students see animal imagery in 3D, hear animal sounds, and observe animal activity online. For systematic learning material development, the research approach uses ADDIE. The research produced animal recognition AR apps for Android smartphones that have undergone a blackbox testing process with 5 valid scenarios. The material evaluation showed 7 aspects of assessment, including the quality of 3D object visualization from AR apps, which scored very good, and 6 other aspects, including the suitability of animal material, which scored good. Sound and language's impact on student's cognitive capacities, including understanding, learning experiences, and motivation. According to the evaluation of AR application material, it can improve students' cognitive abilities in learning to recognize animals, which can be used in the teaching and learning process, and 3D object visualization from AR applications can help students understand learning